Rhizosphere microbiome regulation: Unlocking the potential for plant growth - Chenghua Luo; Yijun He; Yaping Chen (Current Research in Microbial Sciences)
Rhizosphere microbial communities are essential for plant growth and health maintenance, but their recruitment and functions are affected by their interactions with host plants. Finding ways to use the interaction to achieve specific production purposes, so as to reduce the use of chemical fertilizers and pesticides, is an important research approach in the development of green agriculture. To demonstrate the importance of rhizosphere microbial communities and guide practical production applications, this review summarizes the outstanding performance of rhizosphere microbial communities in promoting plant growth and stress tolerance. We also discuss the effect of host plants on their rhizosphere microbes, especially emphasizing the important role of host plant species and genes in the specific recruitment of beneficial microorganisms to improve the plants’ own traits. The aim of this review is to provide valuable insights into developing plant varieties that can consistently recruit specific beneficial microorganisms to improve crop adaptability and productivity, and thus can be applied to green and sustainable agriculture in the future.